Transferrin receptor 1 ablation in satellite cells impedes skeletal muscle regeneration through activation of ferroptosis. Issue 3 (6th May 2021) - Ding, Hongrong; Chen, Shujie; Pan, Xiaohan; Dai, Xiaoshuang; Pan, Guihua; Li, Ze; Mai, Xudong; Tian, Ye; Zhang, Susu; Liu, Bingdong; Cao, Guangchao; Yao, Zhicheng; et al.
Abstract: Background: Satellite cells (SCs) are critical to skeletal muscle regeneration. Inactivation of SCs is linked to skeletal muscle loss. Transferrin receptor 1 (Tfr1) is associated with muscular dysfunction as muscle‐specific deletion of Tfr1 results in growth retardation, metabolic disorder, and lethality, shedding light on the importance of Tfr1 in muscle physiology. However, its physiological function regarding skeletal muscle ageing and regeneration remains unexplored. Methods: RNA sequencing is applied to skeletal muscles of different ages to identify Tfr1 associated to skeletal muscle ageing. Mice with conditional SC ablation of Tfr1 were generated. Between Tfr1 SC/WT and Tfr1 SC/KO ( n = 6–8 mice per group), cardiotoxin was intramuscularly injected, and transverse abdominal muscle was dissected, weighted, and cryosectioned, followed by immunostaining, haematoxylin and eosin staining, and Masson staining. These phenotypical analyses were followed with functional analysis such as flow cytometry, tread mill, Prussian blue staining, and transmission electron microscopy to identify pathological pathways that contribute to regeneration defects. Results: By comparing gene expression between young (2 weeks old, n = 3) and aged (80 weeks old, n = 3) mice among four types of muscles, we identified that Tfr1 expression is declined in muscles of aged mice ( 80% reduction, P < 0.005), so as to its protein level in SCs of aged mice. From in vivo and ex vivo experiments, Tfr1 deletion in SCs results in an irreversible depletion of SCs ( 60% reduction, P < 0.005) and cell‐autonomous defect in SC proliferation and differentiation, leading to skeletal muscle regeneration impairment, followed by labile iron accumulation, lipogenesis, and decreased Gpx4 and Nrf2 protein levels leading to reactive oxygen species scavenger defects. These abnormal phenomena including iron accumulation, activation of unsaturated fatty acid biosynthesis, and lipid peroxidation are orchestrated with the occurrence of ferroptosis in skeletal muscle. Ferroptosis further exacerbates SC proliferation and skeletal muscle regeneration. Ferrostatin‐1, a ferroptosis inhibitor, could not rescue ferroptosis. However, intramuscular administration of lentivirus‐expressing Tfr1 could partially reduce labile iron accumulation, decrease lipogenesis, and promote skeletal muscle regeneration. Most importantly, declined Tfr1 but increased Slc39a14 protein level on cellular membrane contributes to labile iron accumulation in skeletal muscle of aged rodents ( 80 weeks old), leading to activation of ferroptosis in aged skeletal muscle. This is inhibited by ferrostatin‐1 to improve running time ( P = 0.0257) and distance ( P = 0.0248). Conclusions: Satellite cell‐specific deletion of Tfr1 impairs skeletal muscle regeneration with activation of ferroptosis. This phenomenon is recapitulated in skeletal muscle of aged rodents and human sarcopenia. Our study provides mechanistic information for developing novel therapeutic strategies against muscular ageing and diseases.